Routledge handbook of politics in Asia - Hua, Shiping (Routledge, Taylor & Franics Group, 2018)
The comparative study of Asian politics / Shiping Hua -- East Asia / Brian Woodall -- Southeast Asia / Ehito Kimura -- South Asia / Maya Chadda -- Central Asia / Mariya Omelicheva -- East Asia / Dennis Hickey, Dean Chen -- Southeast Asia / Shane Barter and Amanda Boralessa -- South Asia / Arndt Michael -- Central Asia / Roger Kangas -- East Asia / Linjun Wu -- Southeast Asia / Yueting Tong -- South Asia / Amita Batra -- Central Asia / Luca Anceschi -- East Asia / Yu-tzung Chang, Yun-han Chu, and Mark Weatherall -- Southeast Asia / Bridget Welsh, and Kai-Ping Huang -- South Asia / Subrata Kumar Mitra and La Toya Waha -- Central Asia / Nalin Kumar Mohapatra -- China's post-Mao reforms / Jason (Chunlong) Lu, Ting Yan -- China's foreign policy / Baohui Zhang -- Huaxiaism: a new world view by mainland China's political science / Zicheng Ye and Xiaole Zhu -- China foreign energy policy: from realism to idealism / Qinhua Xu -- The adaptation of democracy: india / Ajay K. Mehra -- India's foreign policy / Shibashis Chatterjee -- Japan's foreign policy / Sebastian Maslow -- Multilateral institutional development in Asia / Yong Deng -- Human rights in Asia / Thio Li-ann -- Politics of the internet in Asia / Jason P. Abbott -- Military and politics in Asia / Aurel Croissant and David Kuehn -- The state of democracy in Asia / Amy L. Freedman -- Security in Asian states / Kenneth Boutin -- Nationalism in Asia-Pacific / Kam-yee Law -- Geopolitics and geo-economics in Eurasia and the Indo-Pacific Rim / Peter J. Rimmer -- The politics of ethnicity in Southeast Asia / Joel Selway -- New regionalism and Euroasia / Mikhail A. Molchanov -- Confucianism and the rise of East Asia / Jinghao Zhou -- Is Confucian culture compatible with democracy? / John Fuh-sheng Hsieh -- Hinduism and democracy / Rina Williams, Nandini Deo -- Socialist constitutionalism / Yuxin Ma -- Gender and politics in South Asia / Vidyamali Samarasinghe -- Prospect of comparative Asian political developments / Peter Moody.
Keywords: Asia -- Handbooks, manuals, etc -- Politics and government -- 1945-; Electronic books; Aufsatzsammlung; Japan; Korea; China; Kollektives Gedächtnis